Electrochemical Determination of Diclofenac by Using ZIF-67/g-C3N4 Modified Electrode - Dang Thi Ngoc Hoa; Nguyen Thi Thanh Tu; Le Van Thanh Son; Le Vu Truong Son; Tran Thanh Tam Toan; Pham Le Minh Thong; Dao Ngoc Nhiem; Pham Khac Lieu; Dinh Quang Khieu (Adsorption Science & Technology)
A facial differential pulse voltammetric procedure using a glassy carbon electrode modified with zeolite imidazolate framework-67/graphitic carbon nitride (ZIF-67/g-C3N4) for the diclofenac (DCF) determination is demonstrated. ZIF-67/g-C3N4 with different mass ratios of the components was synthesized in a self-assembly process. The obtained materials were characterized by using X-ray diffraction, scanning electron microscopy (SEM), EDX-mapping, and nitrogen adsorption/desorption isotherms. The peak current varies linearly with the DCF concentration in the range of 0.2–2.2 μmol·L−1 and has a detection limit of 0.071 μmol·L−1. The modified electrode exhibits acceptable repeatability, reproducibility, and selectivity towards DCF. The proposed electrode allows determining DCF in human urine without pretreatment, and the results are comparable with those determined with HPLC.